Building the interaction interfaces: host responses upon infection with microorganisms. (February 2015) - Yamazaki, Akihiro; Hayashi, Makoto
Highlights: Pathogens and symbionts trigger common host responses. These biotic interactions affect plant developmental and physiological processes. Interactions between plants and microorganisms may shape plant community. Abstract : Research fields of plant symbiosis and plant immunity were relatively ignorant with each other until a little while ago. Recently, however, increasing intercommunications between those two fields have begun to provide novel aspects and knowledge for understanding relationships between plants and microorganisms. Here, we review recent reports on plant–microbe interactions, focusing on the infection processes, in order to elucidate plant cellular responses that are triggered by both symbionts and pathogens. Highlighting the core elements of host responses over biotic interactions will provide insights into general mechanisms of plant–microbe interactions.